Numerical analysis for shallow tunnels in weak ground supported by umbrella arch method - Tan, Wooi Leong (2008)
In this work, 2D and 3D numerical studies are performed to evaluate the differences in the estimated ground displacements when different modelling approximations are used for the Pipe Umbrella Arch.